RELATIONSHIPS BETWEEN MOUTHPART STRUCTURES AND IN SITU FEEDING HABITS OF FIVE NERITIC CALANOID COPEPODS IN THE CHUKCHI AND NORTHERN BERING SEAS IN OCTOBER 1988 (17th Symposium on Polar Biology) - オオツカ, ススム; シモズ, マリコ; タニムラ, アツシ; フクチ, ミツオ; ハットリ, ヒロシ; ササキ, ヒロシ; マツダ, オサム; OHTSUKA, Susumu; SHIMOZU, Mariko; TANIMURA, Atsushi; FUKUCHI, Mitsuo; HATTORI, Hiroshi; et al. (National Institute of Polar Research, 1996)
P(論文) The mouthpart structures and gut contents of the following five neritic calanoid copepods collected from the Chukchi and northern Bering Seas during the daytime in October 1988 were examined with scanning electron and light microscopes: Acartia longiremis; Centropages abdominalis; Epilabidocera longipedata; Eurytemora herdmani; Tortanus discaudatus. The sharpness of the mandibular ventralmost tooth and the fine structures of maxillary setae are evidently indicative of feeding habits. The mouthpart of E. herdmani with the lowest ventralmost tooth and regularly spinulose setae on all maxillary endites and endopod mainly suits suspension-feeding, whereas that of T. discaudatus with the sharpest ventralmost tooth and hooked, serrate setae only on the basal endite and endopod is specialized for raptorial feeding. Gut content analyses revealed that A. longiremis, C. abdominalis, E. herdmani and E. longipedata fed on various phytoplankter particles while E. longipedata and T. discaudatus preyed on zooplankters such as copepodids, appendicularians and polychaetes. Although A. longiremis, C. abdominalis and E. longipedata possibly employ both feeding modes, there were some differences in the mouthpart structures and food items. The feeding ecology of the five families containing these five species is briefly reviewed. departmental bulletin paper